REAL CORP 2019: Is this the real World? Perfect smart cities vs. real emotional cities. Proceedings of 24th International Conference on Urban Planning, Regional Development and Information Society. Beiträge zur 24. internationalen Konferenz zu Stadtplanung, Regionalentwicklung und Informationsgesellschaft. - (:unkn) unknown (My University, 2019)
Städte bestehen nicht nur aus Ziegeln, Mörtel, Stahl, Glas und - seit einiger Zeit - Informations- und Kommunikationstechnik. Eine Stadt hat eine Identität, eine "Seele", sie ist emotional - und das ist oft etwas sehr Wichtiges für eine Stadt, ihre Räume und ihre Viertel und natürlich auch für ihre Einwohner. Städte sind ein Zuhause, es gibt Wohlfühlorte genau so wie Gegenden, die man eher vermeidet - abhängig von vielen gemeinsamen und individuellen Faktoren. Was macht den Geist, die Seele einer Stadt oder eines Orts aus? Die REAL CORP 2019 beschäftigte sich mit den Verbindungen und Unterschieden zwischen Standardisierung durch technische Innovation einerseits und dem Streben nach Einzigartigkeit und Individualität andererseits. Der Band gibt sämtliche Beiträge - z.T. peer reviewed - wieder.

REAL CORP 2019 under the topic "Is this the Real World?" tries to explore the common ground as well as differences between Perfect Smart Cities and Real Emotional Cities. The term "Smart Cities" has been excessively used and bears the hope and promise that cities will become more efficient but also more liveable. "Smart Cities Solutions" has also become a major industry with a huge future potential. Cities do not just consist of bricks, mortar, steel, glass and - recently - ICT. A city has an identity, a "spirit", it is emotional, and this is often something very important for a city and its places and districts, and of course for its citizens. Cities are "home", there can be feel-good places as well as areas rather to avoid, depending on many factors: common and individual ones. What makes the "spirit of a city" or a place? Whereas renderings in the Smart City context all too often show almost perfect cities, real cities have their shiny places, but most probably also their "dark sides". What is the situation and the future of "THE REAL WORLD"? What is the relation between longing for "Perfect Smart Cities" and "Real Emotional Cities"? Will cities and neighbourhoods be "standardised" and more look and feel like each other or will they keep their identities? Will this be just decided in market values? Can urban planning support keeping and creating places, spaces and cities - "Real Emotional Cities"? What are the tools for the 21st century city? Of course we must not forget that sustainability and resilience stay primary goals for urban development. REAL CORP 2019 explores the relations and differences between standardisation trough technical innovation on the one hand and the quest for uniqueness and peculiarity on the other hand. The proceedings of this year's conference contain 110 scientific papers; 86 of them were selected after a double-blind, double-stage (for both abstracts and full papers) peer-review process for publication.
Keywords: Stadtentwicklung; Stadtplanung; Regionalentwicklung; Stadtsoziologie; Stadtleben; Lokale Identität; Informationstechnologie; Digitalisierung; Smart City; Stadtsystem